If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x = -8x + -8 Reorder the terms: -10x = -8 + -8x Solving -10x = -8 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -10x + 8x = -8 + -8x + 8x Combine like terms: -10x + 8x = -2x -2x = -8 + -8x + 8x Combine like terms: -8x + 8x = 0 -2x = -8 + 0 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| 28x^3+48x^7= | | (x-1)/2/5/4 | | 4n-6+4n=2 | | 9x^4-24x^3-26x^2+56x-15=0 | | 4x^2-11=26 | | f(x)=9x^4-24x^3-26x^2+56x-15 | | 49v-90=-6v+34 | | -5-8=5x+9x-21x | | 192=3X | | -8x^2=-64 | | (1-4x)(1-3x)=6x(2x-1) | | 6,5/9=x/40 | | (5y+4w-3w-5)= | | N+4N=7N+22 | | 3.6b^3=42.5 | | 6x^2+9=4x^2+17 | | (5cd^-3/10d^5)^-1 | | (14x-28)/2x*8/7 | | 9m^2+12m+36=0 | | 6x-2=-5 | | 4(-5+1.875y)+2y=56 | | 2.3=81-3 | | (x+2)x(x+3)=0 | | 121/2=5m | | 5x^2=3x^2 | | 3x+6=-54 | | y-4=7(x+2) | | 29x=6x-8 | | 28a^9+(-8x)= | | 1/16*1/8 | | 5m=121/2 | | -4(2m-6)+9(m-3)=13-9 |